Perbandingan Dan Analisis Metode Klasifikasi Untuk Menentukan Konsentrasi Jurusan - Indah Hidayanti; Tri Basuki Kurniawan; Afriyudi Afriyudi (UNIVERSITAS INDO GLOBAL MANDIRI)
AbstractHigher education is the organizer of further education after the high school level. Five institutions of higher education, namely universities, institutes, high schools, academies and polytechnics. One of the factors that determine the quality of higher education is the percentage of students' ability to complete their studies on time. This is certainly obtained by choosing the right concentration of students during the lecture period and the academic ability of students. Determination of student concentration specifications is needed to determine the interests and talents of the students themselves. With the selection of the right concentration it is expected that students can graduate on time. At this time students have difficulty in determining the concentration of majors. At Bina Darma University in Palembang, especially in the Faculty of Computer Science, there are Informatics Engineering (IT). At the Faculty of Computer Science, the IT Study Program has a concentration of expertise such as Database, Software, and Network Infrastructure that are in accordance with the IT Study Program curriculum at Bina Darma University. Determination of concentration is carried out at the end of semester 4 or precisely the lecture period for semester 5. However, what happens is that students do not know their interests and abilities. At this time students have difficulty in determining the concentration of majors. The choice of concentration of the department is only based on the wishes of the students or by joining friends, so that there is a need for preference in helping students choose concentration. The methods used in data mining are C4.5 and Naïve Bayes by using the Rapid Miner application as a tool to classify student majors. In this study, it is know that C4.5 algorithm has a high accuracy of 48,06% and Naïve Bayes 42,79%Keywords : C4.5, Naïve Bayes, Klasifikasi Jurusan, Rapid MinerAbstrakPerguruan tinggi merupakan penyelenggara pendidikan lanjutan setelah tingkat sekolah menengah atas. Salah satu faktor yang menentukan kualitas perguruan tinggi yaitu persentasi kemampuan mahasiswa untuk menyelesaikan studi tepat pada waktunya. Hal ini tentunya didapatkan dengan pemilihan konsentrasi mahasiswa yang tepat pada masa perkuliahan serta kemampuan akademis dari mahasiswa. Penentuan spesifikasi konsentrasi mahasiswa sangat dibutuhkan untuk menentukan minat dan bakat mahasiswa itu sendiri. Dengan pemilihan konsentrasi yang tepat diharapkan mahasiswa dapat lulus tepat pada waktunya. Pada saat ini mahasiswa kesulitan dalam menentukan konsentrasi jurusan. Di Universitas Bina Darma Palembang terutama di Fakultas Ilmu Komputer, terdapat Program Studi Teknik Informatika (TI). Pada Fakultas Ilmu Komputer ini, Program Studi TI mempunyai konsentrasi keahlian seperti Database, Software, dan Jaringan Infrastructure yang sesuai dengan kurikulum Program Studi TI di Universitas Bina Darma. Penentuan konsentrasi jurusan yaitu pada akhir semester 4 atau tepatnya masa perkuliahan untuk semester 5. Akan tetapi yang terjadi yaitu mahasiswa tidak tahu minat dan kemampuannya masing-masing. Saat ini mahasiswa kesulitan dalam menentukan pemilihan konsentrasi jurusan. Pemilihan konsentrasi jurusan hanya berdasarkan pada keinginan mahasiswa ataupun ikut-ikutan teman, untuk itu dirasa perlu adanya preferensi dalam membantu mahasiswa memilih konsentrasi. Metode yang digunakan yaitu C4.5 dan Naïve Bayes dengan menggunakan aplikasi Rapid Miner sebagai alat bantu untuk mengklasifikasikan penjurusan mahasiswa. Pada penelitian ini diketahui algoritma C4.5 memiliki tinggkat akurasi 48,06 % dan naïve bayes 42,79%.Kata kunci: C4.5, Naïve Bayes, Klasifikasi Jurusan, Rapid Miner